Fifteenth General Review of Quotas-Notification from the Executive Board to the Board of Governors : 43800. (Policy Papers; Policy Paper, 2020)
On December 20, 2019, the Executive Board notified the Board of Governors that it would not be able to report to the Board of Governors in time to facilitate a vote by the Board of Governors concluding the Fifteenth Review before the end of 2019, as previously envisaged, and that the Executive Board was expected to report to the Board of Governors around mid-January 2020 on the outcome of discussions on the Fifteenth Review, the goals and timetable for the Sixteenth Review, and on the way forward on IMF resources.